NAP SACC UK: protocol for a feasibility cluster randomised controlled trial in nurseries and at home to increase physical activity and healthy eating in children aged 2–4 years. Issue 4 (6th April 2016) - Kipping, R; Jago, R; Metcalfe, C; White, J; Papadaki, A; Campbell, R; Hollingworth, W; Ward, D; Wells, S; Brockman, R; Nicholson, A; Moore, L
Abstract : Introduction: Systematic reviews have identified the lack of intervention studies with young children to prevent obesity. This feasibility study examines the feasibility and acceptability of adapting the Nutrition and Physical Activity Self-Assessment for Child Care (NAP SACC) intervention in the UK to inform a full-scale trial. Methods and analysis: A feasibility cluster randomised controlled trial in 12 nurseries in England, with 6 randomly assigned to the adapted NAP SACC UK intervention: nursery staff will receive training and support from an NAP SACC UK Partner to review the nursery environment (nutrition, physical activity, sedentary behaviours and oral health) and set goals for making changes. Parents will be invited to participate in a digital media-based home component to set goals for making changes in the home. As this is a feasibility study, the sample size was not based on a power calculation but will indicate the likely response rates and intracluster correlations. Measures will be assessed at baseline and 8–10 months later. We will estimate the recruitment rate of nurseries and children and adherence to the intervention and data. Nursery measurements will include the Environmental Policy Assessment and Observation score and the nursery staff's review of the nursery environment. Child measurements will include height and weight to calculate z-score body mass index (zBMI), accelerometer-determined minutes of moderate-to-vigorous physical activity per day and sedentary time, and diet using the Child and Diet Evaluation Tool. Questionnaires with nursery staff and parents will measure mediators. A process evaluation will assess fidelity of intervention delivery and views of participants. Ethics and dissemination: Ethical approval for this study was given by Wales 3 NHS Research Ethics Committee. Findings will be made available through publication in peer-reviewed journals, at conferences and to participants via the University of Bristol website. Data will be available from the University of Bristol Research Data Repository. Trial registration number: ISRCTN16287377.